Effect of Transcutaneous Electrical Nerve Stimulation and Cupping Therapy in The Treatment of Tennis Elbow: A Randomized Controlled Trial (International Journal of Physiotherapy, 2021)
Background: Tennis elbow (TE) is a common disorder of the upper extremities that occurs due to powerful grip and repetitive motions in the wrist joint during various activities. Although several management strategies have discussed some of the methods used to reduce pain and improve elbow and wrist movements, the use of new approaches remains a vigorous option to reach the maximum degree of improvement and complete recovery.Aim: The current study aimed to investigate the effect of Transcutaneous electrical nerve stimulation (TENS) and cupping therapy in treating TE.Methods: One hundred and twenty patients between the ages of 20 and 50 years of both sexes complained of tennis elbow. They were divided randomly into four groups. Group A (n=30) received conventional treatment, group B (n=30) received TENS in addition to conventional treatment, group C (n=30) received cupping therapy with conventional treatment, and group D (n=30) received TENS and cupping therapy plus conventional treatment. Visual analog scale (VAS) was used to assess pain intensity, a hand dynamometer was used to measure pain-free grip strength (PFGS), and a patient-rated tennis elbow evaluation (PRTEE) questionnaire was used to measure pain and disability of the forearm before and after four weeks.Results: There was a significant decrease in VAS, PRTEE score, and an increase in PFGS favoring group D compared to the other groups post-treatment (p < 0.001).Conclusion: The combination of TENS and cupping therapy results in better improvement in TE treatment than conventional therapy, TENS, and cupping therapy alone.